Character and Competence in The Implementation of Living Curriculum in Indonesian Schools Kuala Lumpur - Zobihi, Fa'u; Supriyati, Yetti; Suseno, Muchlas; Ismuni, Mutdi (Sekolah Tinggi Ilmu Ekonomi Indonesia (STEI) Jakarta, 2023)
This article explains the concept of Living curriculum in the world of education which has implications for character and skills through the process of coaching and habituation of students about the values, goals and meaning of life. Through this curriculum students can realize how important it is to behave based on good rules and values. The Life Curriculum is also an activity to develop or strengthen the character and good values possessed by students, this makes students have complex principles for harmonious relationships between humans and their environment. The method used in this study is descriptive analysis, which collects data from several national and international articles related to the living curriculum. Kuala Lumpur Indonesia School is developing the Living curriculum. They aim to equip their students to compete in the future era. Therefore, students must have cognitive, affective, and psychomotor abilities. The development of the Living Curriculum at the Kuala Lumpur Indonesia School emphasizes character building and life skills. Another goal of development is to foster collaboration between parents and schools in educating children, so that they have the ability to have life skills and good character, at home, at school and in the community.